PENGARUH ESG (ENVIRONMENTAL, SOCIAL AND GOVERNANCE), BEBAN UTANG DAN KINERJA KEUANGAN TERHADAP AGRESIVITAS PAJAK (STUDI EMPIRIS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024) - Latifatul Aini; Dinar Ambarita (Jurnal Nusa Akuntansi, 2026)
This study aims to examine and analyze the influence of ESG (Environmental, Social and Governance), debt burden, and financial performance on tax aggressiveness in state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Tax aggressiveness refers to a company's strategy to minimize tax burdens, which can impact state revenue and create inequality within the tax system. The independent variables in this study are ESG score, debt burden (cost of debt), and financial performance, which is proxied by Return on Assets (ROA). The dependent variable is tax aggressiveness, measured using the Effective Tax Rate (ETR). This research uses a quantitative method with an associative approach to determine the relationship between two or more variables. The data used are secondary data, analyzed using panel data regression through Eviews 10 software. The results show that ESG, debt burden, and financial performance simultaneously have a significant effect on tax aggressiveness. Partially, ESG has a negative effect on tax aggressiveness, while debt burden and financial performance have a positive effect. These findings indicate the importance of good corporate governance and sustainability (ESG) in reducing tax aggressiveness practices. The results are also valuable for governments, investors, and company management in formulating ethical tax policies and business strategies.